An Experimental Study on the Effect of Sprint Interval Training Versus Traditional Exercise Programs Among Young Obese Adults.: Life Sciences-Physiotherapy - Gunasekar, Thirulogachandar; Balamurugan, Shivaranjani; Ravi, Murali; K, Muthulakshmi; Cyrus, Bernard Ebenezer; K, Saraswathi; Kaliyaperumal, Balaji (International Journal of Life Science and Pharma Research, 2024)
The aim and objective of the study is that the prevalence of overweight and obesity have peaked in past decades whichresulting in many adverse effects on health of young adults; hence this study is designed to compare the effectiveness of sprintinterval training and traditional exercise program on body mass index (kg/m2), waist circumference (cm), body weight (kg) andblood lipid profiles in young adult with obesity. According to WHO, Obesity has become a global epidemic in both developed anddeveloping countries, which is considered one of the major risk factors for cardiovascular diseases. The American HeartAssociation has recommended reducing the risk of cardiovascular disease by weight loss, which is essential for the obesepopulation. Sprint Interval Training has improved insulin sensitivity, low-density lipoprotein cholesterol [LDL-C], and bodycomposition. Traditional exercises were also effective in improving cardiovascular and metabolic function and consequent reductionin the prevalence of dyslipidemia, hypertension, and insulin resistance. In this comparative study, 30 subjects aged 20-30 with a BodyMass Index >25 were included based on specific selection criteria and divided into two groups. Group A was trained with sprintinterval training, and Group B was trained with traditional exercise training. Each group, A and B, consisting of 15 subjects, wasrecruited from Dr. M.G.R. Educational and Research Institute, Chennai. This study measured Body Mass Index, Waistcircumference, and body weight before and after the intervention in groups A and B. Comparing Posttest values between Group Aand Group B on Body Weight, Body Mass Index, and waist circumference score showed a highly significant difference in meanvalues at P ≤ 0.001 in Group A than Group B. Hence, this study proved that sprint interval training significantly improved inreducing Body mass index, waist circumference, and body weight in obese young adults.